Methods of forensic examination of Nalbuphine - I. О. Besedina (Bulletin of Kharkiv National University of Internal Affairs)
The article discusses the peculiarities of forensic examination of nalbuphine hydrochloride, a prescription medicine that can be purchased without a prescription in many pharmacies. At present, in Ukraine, nalbuphine is not subject to subject-quantitative accounting in healthcare facilities and by pharmaceutical manufacturers, but in some countries it is included in the list of narcotic drugs. It is emphasised that nalbuphine hydrochloride is a synthetic opioid analgesic, which is chemically similar to morphine and phenanthrene. In terms of pharmacological action, it belongs to the group of opioid receptor agonists-antagonists (pentazocine, buprenorphine, butorphanol).